PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP JOB RELEVANT INFORMATION SERTA IMPLIKASINYA PADA SENJANGAN ANGGARAN (STUDI PADA PEMERINTAH DAERAH KABUPATEN BIREUEN) - Rida Fani Bulan (Program Magister Akuntansi Unsyiah, 2011)
The purposes of this research were to know: (1) the effect of budgetary participation on budget objective clarity; (2) the effect between budgetary participation and the clarity of budget objectives on job relevant information simultaneously and partially; (3) the effect of budget, budget objective clarity, and job relevant information on budgetary slack either simultaneously and partially. The result showed that the budgetary participation affected the budget objective clarity. The result also showed that budgetary participation and budget objective clarity influenced simultaneously and partially on job relevant information. The Budgetary participation, budget objective clarity and job relevant information affected simultaneously and partially the budgetary slack. Keywords: Budgetary Participation, Budget objective Clarity, Job Relevant Information, Budgetary Slack